Association of preoperative serum CRP with PD-L1 expression in 508 patients with non-small cell lung cancer: A comprehensive analysis of systemic inflammatory markers. (March 2018) - Akamine, Takaki; Takada, Kazuki; Toyokawa, Gouji; Kinoshita, Fumihiko; Matsubara, Taichi; Kozuma, Yuka; Haratake, Naoki; Takamori, Shinkichi; Hirai, Fumihiko; Tagawa, Tetsuzo; Okamoto, Tatsuro; Yoneshima, Yasuto; et al.
Abstract: Objectives: Programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors have been approved as a standard therapy for metastatic non-small cell lung cancer (NSCLC). Although PD-L1 expression serves as a predictive biomarker for the efficacy of immunotherapy, there are no established biomarkers to predict the expression of PD-L1. The inflammatory markers C-reactive protein (CRP) and neutrophil-lymphocyte ratio (NLR) were recently shown to predict the efficacy of nivolumab for NSCLC patients. Therefore, here we investigated the potential association of PD-L1 expression with systemic inflammatory markers, including CRP, NLR, lymphocyte-monocyte ratio and platelet-lymphocyte ratio. Methods: We retrospectively examined tumor PD-L1 expression in 508 surgically resected primary NSCLC cases by immunohistochemical analysis (cut-off value: 1%). The association of PD-L1 expression with preoperative systemic inflammatory markers was assessed by univariate and multivariate analyses. We generated a PD-L1 association score (A-score) from serum CRP level (cut-off value: 0.3 mg/dl) and smoking status to predict PD-L1 expression. Results: Among the total 508 patients, 188 (37.0%) patients were positive for PD-L1 expression at the 1% cut-off value and 90 (17.5%) had elevated serum CRP level. Multivariate logistic regression revealed that PD-L1 positivity was significantly associated with advanced stage, the presence of vascular invasion and high serum CRP level ( P  = .0336, .0106 and 0.0018, respectively). Though not significant, smoking history tended to be associated with PD-L1 protein expression ( P  = .0717). There was no correlation with other inflammatory markers. Smoking history with elevated CRP level (A-score: 2) was strongly associated with PD-L1 protein expression (odds ratio: 5.18, P  < .0001), while it was inversely associated with EGFR mutation (odds ratio: 0.11, P  < .0001). Conclusions: Our results indicate that among all systemic inflammatory markers examined, serum CRP seems to predict PD-L1 expression in patients with NSCLC however the clinical applicability is limited given the obtained area under the receiver operating characteristic curve values. Highlights: There are no established biomarkers to predict the expression of PD-L1. Association of PD-L1 expression with inflammatory markers was investigated. PD-L1 expression was significantly associated with higher serum CRP level. Serum CRP seems to predict PD-L1 expression however the clinical applicability is limited given the obtained AUC values.